Optimized frame structure using distributed source coding for interactive multiview video streaming - Gene Cheung; Ngai-Man Cheung; Ortega, A. (2009 16th IEEE International Conference on Image Processing (ICIP), 2009)
While multiview video coding typically focuses on the rate-distortion performance of compressing all frames of all views, we address the problem of designing a pre-encoded frame structure for a streaming server to enable a new functionality-interactive multiview switching, where a streaming client can send requests periodically to a server to switch to different views while continuing uninterrupted temporal playback of streaming video. We observe that providing bandwidth-efficient interactive view switching usually comes at the price of additional overall storage. Thus, our goal is to find a frame structure that minimizes the expected transmission rate during interactive multiview streaming, subject to a storage constraint. Noting that standard tools for random access (i.e., I-frame insertion) can be bandwidth-inefficient for this functionality, we propose to automatically generate a structure, combining I-frames, redundant P-frames and Distributed Source Coded (DSC) frames, in a near-optimal fashion to facilitate view switching. We present three new DSC techniques for view switching and discuss how these techniques can be integrated into an optimization framework. We show experimentally that near-optimal coding structures using DSC frames, in addition to I- and P-frames, reduce transmission cost over structures using I-frames only for view switching by up to 28%, and over structures using I- and P-frames only by up to 20% for the same storage cost.